THE RATIONAL CHOICE THEORY IN THE MODERN RELIGIOUS: EXAMPLE OF POSITIVIST AND INTERDISCIPLINARY APPROACH - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
On the basis ofphilosophical andreligious studiesanalysis"rational choice theory", as well as the concept of "religious economy" and "economics of religion" are considered in the context of modern religious.